Q Fever in the First Trimester: A Case Report from Northern Rural New South Wales - Marks, Sarah (Trop Med Infect Dis, 2019)
Pregnant women are significantly more likely to have an asymptomatic acute infection with C. burnetii which, untreated, has been associated with poor obstetric outcomes including miscarriage, stillbirth, intrauterine growth restriction, and premature delivery. As such, Q fever is a potentially under-recognised and treatable cause of adverse pregnancy outcomes in rural Northern New South Wales, with testing of Q fever polymerase chain reaction (PCR)—whether on maternal sera or placental tissue—not currently recommended by the Perinatal Society of Australia and New Zealand for Stillbirth.